1995
DOI: 10.1128/jcm.33.8.2176-2178.1995
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of preservation media for storage of stool samples

Abstract: Transportation of clinical samples and long-term recoverability of pathogens are critical to epidemiological studies, particularly when conditions do not permit immediate processing. This study confirms that Cary-Blair medium (CB) is suitable for the preservation of Salmonella and Shigella isolates for more than 2 weeks at 25, 4, or ؊70 C. Campylobacter jejuni was not recovered after 2 days of storage in CB at 25 C when an inoculum of 12 ؋ 10 8 cells per ml was used. Lower temperatures supported the recovery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 11 publications
0
19
0
1
Order By: Relevance
“…Bacteria that are commonly considered pathogenic in primates (Salmonella, Shigella, Campylobacter, and Yersinia) were not detected, supporting the assumption that they are not part of the normal enteric flora. Although storage of feces without cryoprotectant in liquid nitrogen has been shown to be effective for sustaining the viability of enteric bacteria [Dan et al, 1989], other studies have suggested that the addition of freezing mediums enhances the recovery of enteropathogens, especially Campylobacter [Wasfy et al, 1995]. Therefore, we cannot state that these agents are not present in wild lemurs.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Bacteria that are commonly considered pathogenic in primates (Salmonella, Shigella, Campylobacter, and Yersinia) were not detected, supporting the assumption that they are not part of the normal enteric flora. Although storage of feces without cryoprotectant in liquid nitrogen has been shown to be effective for sustaining the viability of enteric bacteria [Dan et al, 1989], other studies have suggested that the addition of freezing mediums enhances the recovery of enteropathogens, especially Campylobacter [Wasfy et al, 1995]. Therefore, we cannot state that these agents are not present in wild lemurs.…”
Section: Discussionmentioning
confidence: 84%
“…Approximately 1 cc of feces was placed into the transport medium (ParaPak; Meridian Diagnostics, Cincinnati, OH) for examination for parasite ova. If sufficient feces were obtained, a second 1-cc sample was frozen (without cryoprotectant) in liquid nitrogen for bacterial culture [Dan et al, 1989;Wasfy et al, 1995].…”
Section: Sample Collectionmentioning
confidence: 99%
“…27 The reduced viability of organisms stored in phosphate buffered glycerol saline in that study may have in part been due to the storage temperature of À20°C rather than À80°C, because it has been demonstrated that lower temperatures enhance bacterial survival. 26 Cryopreserving media such as Cary-Blair media, skim milk and Amies media, have been used to store stool for later analysis [29][30][31] , however, some of these media are less effective than 10% glycerol solutions at retaining microbial viability and others are unsuitable to be administered into a patient's gastrointestinal tract as they are untested on humans.…”
Section: Discussionmentioning
confidence: 99%
“…Since the addition of blood as a cryopreservant is useful due to the presence of some factors contributing to the buffering, osmotic, homeostatic, and cryoprotective properties which are necessary for the survival of certain bacteria , sheep blood was used in the present study. However, unforeseen findings have been noticed.…”
Section: Resultsmentioning
confidence: 99%